Legado imperecedero de un botánico costarricense singular – Jorge Gómez Laurito (1947-2014) in memoriam - Morales, Carlos O. (Universidad de Costa Rica, 2014)
Legado imperecedero de un botánico costarricense singular– Jorge Gómez Laurito (1947-2014) in memoriam Carlos O. Morales (carlos.moralessanchez@ucr.ac.cr) y Rodolfo Ortiz Vargas (rortiz23v@hotmail.com), Escuela de Biología, Universidad de Costa Rica11501-2060 San José, Costa Rica AbstractThe life and professional work of the Costa Rican botanist Jorge Gómez Laurito (1947-2014) are here depicted. His 90 scientific publications and 50 new plant taxa (including a family, a genus, and 48 species) represent a long-lasting legacy. The description and publication of Ticodendraceae was his most notable professional achievement.